Physiological demands of racket sports: a systematic review - Cádiz Gallardo, María Pía; Pradas de la Fuente, Francisco; Moreno-Azze, Alejandro; Carrasco Páez, Luis (Frontiers in Psychology, 2023)
The practice of racket sports has had an exponential growth in the last decade, along with it, the scientific interest in researching the different disciplines: badminton, padel, table tennis, tennis and squash. However, most research has focused on the technical and tactical field. Therefore, the aim of this review is to analyze and compare the indicators of the internal load of each sport: heart rate (HR), maximum oxygen consumption (VO2max), oxygen consumption (VO2) and lactate (LA) in order to reset physiological references to adjust the training of the players and also use these references to propose the practice of these sports for healthy purposes to the general population. PRISMA Guidelines for Systematic Review were used to search for articles that met the inclusion criteria in three databases: Web of Science, Pubmed, and Sportdiscus. The search was performed between January 2010, and September 2022. Finally, a total 27 records were included for analysis in this study.The main findings were related to the differences in the intensity rates between sports. The highest lactate concentrations and heart values were found in badminton in the intensity of effort values (whose highest values were found in badminton) 10.11 (±4.99) mmol/L and 182.6 (± 2.7) bpm respectively, whereas table tennis showed the lowest ones 1.2 (± 0.4) mmol/L, and 103.99 (±15.09) bpm respectively. The highest mean VO2 was found in table tennis with a value of 36.8 (±13.2) ml/kg/min and the lowest in tennis with a value of 26.6 (±2.7) ml/kg/min. The highest VO2max was found in tennis players 58.0 (± 4.6) ml/kg/min, and the lowest value was in table tennis with a value of 42.9 (± 4.2) ml/kg/min. Due to the fact that most of the studies were carried out on elite male players, future research should focus on amateur and female level players.